Answers

2015-03-31T23:06:28+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Step 1:  x²-6/5 x -2/5 = 0 divding equation with 5
step 2 : x²-6x/5 = 2/5
step 3: x²-6x/5 + (3/5)² = 2/5 +(3/5)²     adding (3/5)² on both sides
step 4: (x- 3/5)² = 2/5 + 9/25
step 5: (x- 3/5)² = 19/25
step 6: x-3/5=√19/√25
step 7: x = 3/5+√19/5
so x = 3+√19/5
s0 x = 3+√19/5 or 3-√19/5
this is the completing square method
2 5 2
:) plz click on ty and mark it as best:)
ade add cheyyalani ela thelustundi?
akkada 6/5 undi kada ala edina no. iste danini 2 tho divide cheste a-b 2 lo b manaku vastubdi ade 3/5 oknaa??
ok
gd
2015-03-31T23:17:23+05:30
Completing the square:
The method is used to solve a quadratic equation,
The following steps  to solve the given equation will make you understand it:

STEP 1:
=0
As the name suggests, we need to complete the squares in it,
So in
5x²-6x-2=0
divide the middle term by 2 and square the quotient so in here we get

5x²-6x+(3)²-2=0+9

we add 9 on the other so that there is no increments or decrements  in the equation , 

STEP 2:

Now you would see that
5x²-6x+(3)²-2=0+9  

=>  5x²-6x+(3)² = 9+2

=> 5x²-6x+(3)² = 11

  Divide the equation by 5 (both side , so that the first term's coefficient  becomes 1. 

This gives   x²- frac{6}{5} x+( frac{9}{5} ) =   frac{11}{5} 
 x²- frac{6}{5} x+( frac{9}{5} ) forms an identity i.e. (a-b)²=a²-2ab+b²

So using the identity we form it as;

(x-3)²=11/5

so x=3+√11/5  or  3-√11/5


 \frac{11}{5}        





0